When the Dignity of Teachers is Underestimated and the Allowance of the House of Representatives is Perpetuated, An Analysis of Inequality in Education Management - Mohammad Fikri (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2025)
The paradox of education in Indonesia is clearly seen through the inequality between the budget for the political elite and the condition of vocational schools at the grassroots level. SMK Nurul Qarnain, a Visual Communication Design major established in 2023 with around 180 students, faces limited facilities, including the absence of a computer laboratory. The policy allows students to bring personal laptops as an adaptive solution that reflects the creativity of pesantren-based education management. Meanwhile, the large salaries and allowances of members of the House of Representatives and the discourse on teacher salaries cause fiscal injustice and weaken the legitimacy of public policy. The qualitative analysis of the case study shows that the limitations of facilities encourage managerial innovation, but still affirm the urgency of redistributing the education budget so that vocational schools receive proportionate support. These findings strengthen academic discussions on the relationship between fiscal justice, policy legitimacy, and the sustainability of vocational education in Indonesia.